2021
DOI: 10.3390/ijms22189926
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and Anti-Angiogenic Treatment in Prostate Cancer: Mechanisms of Action and Molecular Targets

Abstract: Prostate cancer (PC) is the most common cancer in men and the second leading cause of cancer-related death worldwide. Many therapeutic advances over the last two decades have led to an improvement in the survival of patients with metastatic PC, yet the majority of these patients still succumb to their disease. Antiagiogenic therapies have shown substantial benefits for many types of cancer but only a marginal benefit for PC. Ongoing clinical trials investigate antiangiogenic monotherapies or combination therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 149 publications
(180 reference statements)
0
40
0
Order By: Relevance
“…However, clinical efficacy of VEGFtargeted drugs has vital limitations. Although phase 3 trials have demonstrated that use of anti-angiogenic agents leads to significant improvements in overall survival (OS) for several cancers, such as advanced-stage CRC, RCC, and HCC, it is also associated with a failure to improve OS in other cancers, such as breast cancer, glioblastoma, pancreatic ductal adenocarcinoma (PDAC) and prostate cancer (10)(11)(12)(13). Carvalho B et al discovered that, in glioblastoma, c-Met overexpression is associated with a time-to-progression (TTP) after bevacizumab of 3 months (95% CI, 1.5-4.5), compared with a TTP of 7 months (95% CI, 4.6-9.4) among patients with low or no expression of c-Met (p = 0.05).…”
Section: The Resistance To Antiangiogenic Therapymentioning
confidence: 99%
“…However, clinical efficacy of VEGFtargeted drugs has vital limitations. Although phase 3 trials have demonstrated that use of anti-angiogenic agents leads to significant improvements in overall survival (OS) for several cancers, such as advanced-stage CRC, RCC, and HCC, it is also associated with a failure to improve OS in other cancers, such as breast cancer, glioblastoma, pancreatic ductal adenocarcinoma (PDAC) and prostate cancer (10)(11)(12)(13). Carvalho B et al discovered that, in glioblastoma, c-Met overexpression is associated with a time-to-progression (TTP) after bevacizumab of 3 months (95% CI, 1.5-4.5), compared with a TTP of 7 months (95% CI, 4.6-9.4) among patients with low or no expression of c-Met (p = 0.05).…”
Section: The Resistance To Antiangiogenic Therapymentioning
confidence: 99%
“…We sequenced RNA from 52,680 cells at eight time points (stem cells -1, 3, 4, 5, 6, 7, 14 and 21 days of differentiation, pooling 20-30 aggregates or 15-20 organoids per time point) (Table S1). At each time point, we combined and dissociated tissues from both cell lines together, and subsequently demultiplexed the sequencing data using single nucleotide polymorphisms (SNPs) differing between the two individuals (demuxlet (Kang et al, 2018)). After quality control, we integrated the datasets using cluster similarity spectrum (CSS (He et al, 2020)) and visualized cell transcriptomes in a Uniform Manifold Approxima- tion and Projection (UMAP (McInnes et al, 2018)) embedding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MiRNAs could regulate endothelial cells via non-cell-autonomous, as well as cell-autonomous techniques, and therefore control angiogenesis and PCa progression. 55 Thus, single miRNAs or miRNA expression profiles could be potential biomarkers for PCa based on their stability and detectability in biopsy tissue and body fluids. 56 , 57 In this study, we selected seven miRNAs that were involved in PCa.…”
Section: Discussionmentioning
confidence: 99%